Clinical and Histopathological Features of Patients with Systemic Sclerosis Undergoing Endomyocardial Biopsy - Mueller, Karin A. L.; Mueller, Iris I.; Eppler, David; Zuern, Christine S.; Seizer, Peter; Kramer, Ulrich; Koetter, Ina; Roecken, Martin; Kandolf, Reinhard; Gawaz, Meinrad; Geisler, Tobias; Henes, Joerg C.; et al. (PloS one, 2015)
Cardiac involvement in systemic sclerosis (SSc) is associated with a variable phenotype including heart failure, arrhythmias and pulmonary hypertension. The aim of the present study was to evaluate clinical characteristics, histopathological findings and outcome of patients with SSc and a clinical phenotype suggesting cardiac involvement. 25 patients with SSc and clinical signs of cardiac involvement were included between June 2007 and December 2010. They underwent routine clinical work-up including laboratory testing, echocardiography, left and right heart catheterization, holter recordings and endomyocardial biopsy. Primary endpoint (EP) was defined as the combination of cardiovascular death, arrhythmic endpoints (defined as appropriate discharge of implantable cardioverter defibrillator (ICD)) or rehospitalization due to heart failure. The majority of patients presented with slightly impaired left ventricular function (mean LVEF 54.1±9.0%, determined by echocardiography). Endomyocardial biopsies detected cardiac fibrosis in all patients with a variable area percentage of 8% to 32%. Cardiac inflammation was diagnosed as follows: No inflammation in 3.8%, isolated inflammatory cells in 38.5%, a few foci of inflammation in 30.8%, several foci of inflammation in 15.4%, and pronounced inflammation in 7.7% of patients. During follow up (FU) (22.5 months), seven (28%) patients reached the primary EP. Patients with subsequent events showed a higher degree of fibrosis and inflammation in the myocardium by trend. While patients with an inflammation grade 0 or 1 showed an event rate of 18.2%, the subgroup of patients with an inflammation grade 2 presented with an event rate of 25% versus an event rate of 50% in the subgroup of patients with an inflammation grade 3 and 4, respectively (p=0.193). Furthermore, the subgroup of patients with fibrosis grade 1 showed an event rate of 11%, patients with fibrosis grade 2 and 3 presented with an event rate of 33% and 42% respectively (p = 0.160). Patients with SSc and clinical signs of cardiac involvement presented with mildly impaired LVEF. Prognosis was poor with an event rate of 28% within 22.5 months FU and was associated with the degree of cardiac inflammation and fibrosis.